Komunikasi Antarpribadi sebagai Sarana Rekonsiliasi dan Penerimaan Diri dalam Film A Silent Voice - Muhammad Farid Firdausy; Dony Kristian; Johantan Alfando WS (MAN 4 Kota Pekanbaru, 2026)
This study examines interpersonal communication as a mechanism for reconciliation and self-acceptance in the film A Silent Voice. The film portrays the relationship between Shoya Ishida, a former perpetrator of bullying, and Shouko Nishimiya, a deaf student who experienced bullying and social exclusion. This research employed a qualitative descriptive approach using Krippendorff’s content analysis method. The data consisted of dialogues, scenes, and character expressions that reflect interpersonal communication dynamics throughout the narrative. The analysis was based on the dimensions of interpersonal communication, including openness, empathy, supportiveness, positiveness, and equality, as well as relevant psychological communication aspects. The findings indicate that interpersonal communication develops progressively from ineffective interactions characterized by trauma, lack of empathy, and inequality toward more constructive communication patterns. Feelings of guilt and regret encourage openness, which subsequently facilitates empathy, support, and positive interpersonal attitudes. These communication processes contribute to relationship restoration, reconciliation, and self-acceptance among the main characters. The study concludes that interpersonal communication functions as an essential mechanism for resolving interpersonal conflict and rebuilding damaged social relationships. This research enriches interpersonal communication studies by demonstrating how communication dynamics contribute to reconciliation and self-acceptance within media narratives.